Empowering Youth for Sustainable Energy Consumption - Nursida Arif; Maria Emerita Indraningrum Shrestha; Laifa Rahmawati; Ulfa Hidayati (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
This paper aims to assess the understanding and attitudes of youth towards energy conservation in Nepal and Indonesia. This research used a quantitative mixed methods approach, including questionnaires and focus group discussions with 101 Nepalese and Indonesian respondents. Qualitative data was obtained from the results of FGDs with 15 respondents from each country. The results show that the training has greatly impacted understanding related to energy conservation. Before being given the training, the level of awareness was 38%. After being given the training, it increased to 65%. The results of the FGD also show that this awareness program has opened the participants' eyes to become aware of energy saving and energy conservation, including water conservation. The study concludes that empowering young people to take action is critical to achieving sustainable energy consumption and highlights the importance of targeting consumer behavior to achieve sustainable energy savings and encourage sustainable consumption patterns. This study also provides insight into the potential of young people to encourage wise energy behavior throughout society and contribute to achieving sustainable energy consumption.